Comparison of different model updating algorithms to detect damage in beam structure using mode shape data - Nur Atikah Zainudin, 1993-, author; Norhisham Bakhary, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia